Association between cholecystectomy and intestinal cancer: a national record linkage study. - Goldacre, M; Wotton, C; Abisgold, J; Yeates, D; Collins, J (2012)
OBJECTIVE: To investigate the risk of intestinal cancer in a cohort of people who had undergone cholecystectomy for gallstones, and in a cohort of people who had been hospitalized for gallbladder disease but had not undergone cholecystectomy. BACKGROUND: Some investigators have suggested that cholecystectomy increases the risk of intestinal cancer. Despite extensive study, the evidence remains inconclusive. If there is doubt about safety, the question arises of whether patients considering the operation should be told of a possible risk. It is also increasingly clear that there are noncausal associations between gallstones and intestinal cancer. METHOD: Analysis of record-linked hospital admission and mortality statistics for England from 1998 to 2008; calculation of ratio of rates of cancers in the cholecystectomy cohort and the gallbladder disease cohort compared with a control cohort. RESULTS: : In the first year after cholecystectomy, the rate ratios for cancer of the small intestine, colon, and rectum were significantly high at, respectively, 4.6 (95% confidence interval 3.9-5.5), 2.0 (1.9-2.1), and 1.7 (1.6-1.9). Rates of these cancers were also significantly high in people with gallstones without cholecystectomy. By 8 to 10 years after cholecystectomy, rate ratios had declined to nonsignificant levels. CONCLUSIONS: These cancers are associated with gallstones. The highest elevation of risk of cancer after cholecystectomy was at the shortest time interval after operation. Thereafter, the level of risk in the cholecystectomy and control cohorts gradually converged. The association in this study, between cholecystectomy and intestinal cancer, is very unlikely to be causal. Intestinal cancers are, on occasion, initially misdiagnosed as gallbladder disease.